Selection Benefits of Below-Market Pay in Social-Mission Organizations: Effects on Individual Performance and Team Cooperation - Chen, Clara Xiaoling; Pesch, Heather L.; Wang, Laura W. (The Accounting Review, 2020)
ABSTRACT Many organizations whose core purpose is to advance a social mission pay employees below-market wages. We investigate two under-appreciated benefits of below-market pay in these social-mission organizations. In a series of experiments, we predict and find that, holding employees' outside opportunities constant, those attracted to social-mission organizations that pay below-market wages perform better individually and cooperate more effectively in teams than those attracted to social-mission organizations that pay higher wages. The individual performance effect arises because below-market pay facilitates the selection of value-congruent employees who are naturally inclined to work hard for the organizational mission. The team cooperation effect arises because employees expect team members who have selected a social-mission job that pays below market to be more value-congruent and, therefore, more cooperative than those who have selected a social-mission job that pays higher wages. Collectively, we demonstrate that in social-mission organizations, offering below-market pay can yield selection benefits.